MENINGKATKAN KEMAMPUAN MENGENAL WARNA PRIMER MELALUI PERMAINAN LEGO BAGI ANAK TUNAGRAHITA RINGAN (Single Subject Research Kelas II C di SLB Negeri Kota Pariaman) - Riri - Rahayu (Universitas Negeri Padang, 2014)
Research this in the background a child light tunagrahita class II C in SLB country city Pariaman who have problems in color know primary good mention color, showing color, and color matching. From there, researchers interested to do research about increase ability color knowing primary through lego game. Research this aims for prove whether the lego game effective to Increase Ability Color Knowing Primary Through Lego Game to child Light Tunagrahita. This research was conducted in SLB Pariaman. This type of research is experimental research in the form of SSR (Single Subject Research). Research experiment is an experiment that is used to examine an event or phenomenon that appears to a particular situation either positive or negative. This study used a design AB, according to Sunanto Juang (2005:54), AB design procedure is prepared on the basis of baseline logic, the logic of the baseline shows a measurement repeatability of behavior on at least two conditions, namely: baseline conditions (A) and intervention condition (B). The results of this study indicate the baseline condition (A) the ability of the child to know the primary colors vary from observation to observation of the first three results are 0% observations fourth to seventh hasinya 33.3% of children were able to meyebutkan color, showing the colors, and the color match is only one color that is the color yellow. In the intervention condition (B) after treated with composing and arranging activities chunks of plastic shaped blocks into the shape of small objects eg tower, seen from the last three treatments on observations obtained thirteenth to fifteenth ability to recognize primary colors with three color lego game result 100%. This indicates that lego games can improve children's ability to recognize the colors on mild mental retardation.